2002
DOI: 10.1073/pnas.132076299
|View full text |Cite
|
Sign up to set email alerts
|

Inosine induces axonal rewiring and improves behavioral outcome after stroke

Abstract: Cerebral infarct (stroke) often causes devastating and irreversible losses of function, in part because of the brain's limited capacity for anatomical reorganization. The purine nucleoside inosine has previously been shown to induce neurons to express a set of growthassociated proteins and to extend axons in culture and in vivo. We show here that in adult rats with unilateral cortical infarcts, inosine stimulated neurons on the undamaged side of the brain to extend new projections to denervated areas of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
180
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(186 citation statements)
references
References 47 publications
(70 reference statements)
5
180
0
1
Order By: Relevance
“…Although our study does not provide direct evidence of a relationship between functional recovery and neuroanatomical reorganization, previous studies have shown that the temporal pattern of functional recovery correlates with neuroanatomical alterations, such as peri-and contralesional synaptogenesis (Stroemer et al, 1995) and contralesional dendritic sprouting (Jones and Schallert, 1992) after cortical brain injury. Furthermore, pharmacological stimulation of neuronal sprouting has been shown to improve behavioral performance (Chen et al, 2002;Kawamata et al, 1997;Stroemer et al, 1998). The lack of a direct correlation between early functional recovery and neuroanatomical changes in our study may be explained by insensitivity of the neuroanatomical tracer techniques to detect initial changes in projection patterns.…”
Section: Correlation Between Brain Reorganization and Functional Recomentioning
confidence: 61%
“…Although our study does not provide direct evidence of a relationship between functional recovery and neuroanatomical reorganization, previous studies have shown that the temporal pattern of functional recovery correlates with neuroanatomical alterations, such as peri-and contralesional synaptogenesis (Stroemer et al, 1995) and contralesional dendritic sprouting (Jones and Schallert, 1992) after cortical brain injury. Furthermore, pharmacological stimulation of neuronal sprouting has been shown to improve behavioral performance (Chen et al, 2002;Kawamata et al, 1997;Stroemer et al, 1998). The lack of a direct correlation between early functional recovery and neuroanatomical changes in our study may be explained by insensitivity of the neuroanatomical tracer techniques to detect initial changes in projection patterns.…”
Section: Correlation Between Brain Reorganization and Functional Recomentioning
confidence: 61%
“…After either a unilateral transection of the corticospinal tract or a unilateral stroke, inosine causes layer five pyramidal cells on the undamaged side of the brain to extend axon collaterals that cross the midline into the denervated side of the spinal cord (10), leading to improved performance with the denervated forepaw (8). The possibility that Mst3b mediates these effects suggests that further studies on how this kinase is regulated may not only enhance our basic understanding of axon growth, but may also be of benefit in the treatment of CNS injury.…”
Section: Discussionmentioning
confidence: 99%
“…The purine nucleoside inosine stimulates axon outgrowth in certain types of neurons in culture and in vivo after CNS injury (6)(7)(8)(9)(10). The purine analog 6-thioguanine (6-TG), on the other hand, blocks outgrowth induced by neurotrophic factors (9,11,12), and this effect is paralleled by the inhibition of a previously unidentified 45-50 kDa serine-threonine protein kinase (13).…”
mentioning
confidence: 99%
“…In the recent years, inosine has been reported to have important effects on the injured nervous system. Thus, administration of inosine in vivo can induce massive sprouting of the normal corticospinal tract into the lesioned side of the cord, 14 stimulate significant axonal rewiring and improve functional outcome after stroke, 28 and protect axotomized retinal ganglion cells from optic nerve transection. 19,20 Inosine is also capable of protecting astrocytes and neurons against hypoxia, ischemia and zinc sulfate in vitro.…”
Section: Discussionmentioning
confidence: 99%